2011
DOI: 10.1002/app.34640
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun magnetic fibrillar polyarylene ether nitriles nanocomposites reinforced with Fe‐phthalocyanine/Fe3O4 hybrid microspheres

Abstract: The electrospinning method has been employed to fabricate ultrafine nanofibers of high-performance polyarylene ether nitriles (PEN) and PEN/Fephthalocyanine/Fe 3 O 4 nanocomposite fibers for the first time. Through optimizing the operational conditions, such as polymer concentration, applied electric voltage, federate, and distance between needle tip and collector, beadfree and uniform fibers with smooth surfaces and certain diameters were obtained. The morphology of the PEN nanofibers is correlated to the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…However, when PLLA is mixed with other materials, the biocompatibility of these additives becomes an important concern. Previous studies have shown that Fe 3 O 4 nanoparticles have an osteogenic effect on bone cells [26,28,37]. Chang et al (2015) mixed Fe 3 O 4 nanoparticles into PLLA to form a biodegradable and radiopaque material for X-ray imaging-enhanced bone screws.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when PLLA is mixed with other materials, the biocompatibility of these additives becomes an important concern. Previous studies have shown that Fe 3 O 4 nanoparticles have an osteogenic effect on bone cells [26,28,37]. Chang et al (2015) mixed Fe 3 O 4 nanoparticles into PLLA to form a biodegradable and radiopaque material for X-ray imaging-enhanced bone screws.…”
Section: Discussionmentioning
confidence: 99%
“…The literature contains many studies on the incorporation of Fe 3 O 4 nanoparticles into nanofibers using an electrospinning technique [28,29,31,37,39,40]. However, most of these studies focus on the physical properties of the nanofibers or the development of novel fabrication techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce crystallinity and therefore to improve the processability of PEN by molecular design, some noncoplanar and twisted structures, such as PP, BPA, PPL and hydroquinone sulfonic acid sodium salt (SHQ), were incorporated in the backbone. Fanbin Meng et al used a PEN copolymer (P16 in figure 4) derived from BPA and resorcinol monomers as an electrospun fiber matrix [65,66]. Iron phthalocyanine (FePc) was mixed with P16 in DMF and then, materials with various size distributions and morphologies were fabricated by modulating the P16 concentration, electric voltage, and distance between needle and collector.…”
Section: Poly(arylene Ether Nitrile) (Pen)mentioning
confidence: 99%
“…Therefore, PEN would exhibit remarkable advantages when used for preparing polymer mats compared with the polymer matrix mentioned above. Until now, we have prepared various PEN fibers, which exhibit excellent thermal and mechanical properties . Recently, carboxylic PEN fiber mats were developed for adsorption of Cu 2+ and a maximum adsorption capacity of 52.77 mg g −1 was obtained .…”
Section: Introductionmentioning
confidence: 99%
“…Until now, we have prepared various PEN fibers, which exhibit excellent thermal and mechanical properties. [46][47][48] Recently, carboxylic PEN fiber mats were developed for adsorption of Cu 2+ and a maximum adsorption capacity of 52.77 mg g −1 was obtained. 49 Nonetheless, the limited adsorption capacity still cannot satisfy the requirements for the removal of heavy metal ions.…”
Section: Introductionmentioning
confidence: 99%